PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION PADA KARYAWAN PURI SANTRIAN SANUR - Pristayati, Luh Putu Mila; Adnyani, I Gusti Ayu dewi (E-Jurnal Manajemen, 2017)
The purpose of this study was to determine the effect of job satisfaction and organizational commitment to employee turnover intention. This research is associative causative aimed mengetahuai influence or relationship between two or more variables. The study was conducted at the Sanur Beach Hotel Sanur. The number of samples taken as many as 93 employees, with a sample random sampling method. Data collected through observation, interviews, and questionnaires. Data analysis technique used is multiple linear regression. Based on the analysis found that job satisfaction and organizational commitment negatively affect turnover intention. This shows that the higher job satisfaction felt by employees, the lower the level of turnover intention. The higher the organizational commitment of employees, the lower the rate of employee turnover intention because it already has a commitment to remain at the company.
Keywords: Job Satisfaction, Organizational Commitment, Turnover Intention